STUDI DESKRIPTIF PADA PROFIL PERILAKU ADIKSI GAME ONLINE SISWA KELAS XI SMAN 10 PANDEGLANG - Widiatmoko, Mualwi; Ardini, Fadhila Malasari; Dwiyanti, Ayi (Institut Daarul Qur'an Jakarta, Indonesia, 2022)
The purpose of this study was to reveal the data and facts about the level of online game addiction among students. This study used a quantitative approach with a descriptive method. The subjects in the study were students of class XI SMA Negeri 10 Pandeglang for the Academic Year 2021/2022, which were 531 students. The data in this study was analyzed using descriptive statistics and the percentage technique. The results showed that 70.37% of students are currently in a state of high addiction, which means students feel uncontrollable compulsions in themselves to repeat the behavior of playing online games and don't care about the negative consequences that come with them. Meanwhile, 29.63% of students are currently in the low addiction category, namely students are able to control their compulsions to play online games and care about the negative consequences that come with them